Improving Students' Ability in Understanding the Meaning of Faith in Allah's Apostles through the Student Teams Achievement Division Method at SD Negeri 091717 Durian Banggal - Purba, Lisnawati; Marwaiyah; Ponirin; Musri; Damanik, Nila Karmila (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the ability of fourth grade elementary school students to understand the meaning of faith in the apostles of Allah through the application of the Student Teams Achievement Division (STAD) cooperative learning method. The background of this study is the low understanding of students towards the concept of faith in the apostles of Allah, which is indicated by learning outcomes that have not met the minimum completion standards. The STAD method was chosen because it focuses on group cooperation and individual responsibility, so it is expected to improve students' understanding and learning outcomes. This study uses a classroom action approach (CAR) which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of the study were fourth grade elementary school students with a total of 30 participants. Data collection techniques were carried out through evaluation tests, observations, and documentation. The data obtained were analyzed descriptively quantitatively and qualitatively. The results of the study showed that the application of the STAD method can improve students' understanding of the meaning of faith in the apostles of Allah. In cycle I, the percentage of student learning completion reached 70%, while in cycle II it increased to 90%. In addition, student activity and participation in the learning process also showed a significant increase. Thus, the STAD method has proven effective in improving students' ability to understand the meaning of faith in the apostles of Allah. It is recommended for educators to apply this method as an alternative to innovative and enjoyable learning, especially in Islamic Religious Education learning. In addition, it is expected that similar research can be conducted at different grade levels or broader materials to enrich the findings in the application of the STAD method.